Reliability of Ultrasound Based Compressibility of the Lower Leg Anterior Tibial Muscle Compartment in Healthy Volunteers - Kay van Heeswijk; Daniëlle Spek; Jesse Muijsenberg; Loes Janssen; Michiel Winkes; Adwin R. Hoogeveen; Marc Scheltinga (International Journal of Sports Physical Therapy)
# Background